1992
DOI: 10.1128/jb.174.23.7848-7853.1992
|View full text |Cite
|
Sign up to set email alerts
|

A second gene for a secreted aspartate proteinase in Candida albicans

Abstract: The gene (PRAII) encoding a secreted aspartate proteinase of Candida albicans has been cloned and sequenced. The nucleotide and deduced amino acid sequences ofPRAII are 77 and 73% identical, respectively, with the reported sequences of PRAIO also cloned from C. albicans. Southern analyses indicated that the genome of each strain examined (ATCC 10231 and ATCC 10261) contains PRAIO and PRAII. Northern (RNA) analyses showed that PRAII was expressed at a much higher level than was PRA10 when secretion of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 23 publications
(19 reference statements)
8
61
0
Order By: Relevance
“…Sullivan, unpublished). An earlier report by Wright et al (1992) had indicated some expression of Sapl in 10261 but the full-length probe used in that experiment would have allowed cross-hybridization to occur. It is clear then that evidence from both mRNA and secreted protein levels shows that Sap2 is the major isoenzyme expressed and that strain 10231 is a significantly greater producer of Sap3 than is 10261 under the conditions used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sullivan, unpublished). An earlier report by Wright et al (1992) had indicated some expression of Sapl in 10261 but the full-length probe used in that experiment would have allowed cross-hybridization to occur. It is clear then that evidence from both mRNA and secreted protein levels shows that Sap2 is the major isoenzyme expressed and that strain 10231 is a significantly greater producer of Sap3 than is 10261 under the conditions used.…”
Section: Discussionmentioning
confidence: 99%
“…It is based o n the well-known ability of aspartic proteinases, with their generally low isoelectric points, to bind to anionexchange resins, and was first used by Remold et al (1968) for Candida Sap. Two such steps have been employed in this study: the 'traditional' DEAE chromatography (in this case as per Riichel, 1981 and Wright et al, 1992) followed by a much faster and higher resolution separation with Mono Q (strong anion exchanger). However, it was not necessary to include the DEAE step as can be seen in Fig.…”
Section: Purification Of Sap2 and Sap3mentioning
confidence: 99%
See 1 more Smart Citation
“…Six C. albicans genes were selected for the study: the multiple-copy-number 18S rRNA gene, the actin (ACT1) gene (10), the EFB1 gene (11), the secreted aspartic proteinase 2 (SAP2) gene (26), and the alcohol dehydrogenase (Adh) 1 and 2 (ADH1 and ADH2) genes (2,24). PCR primers for detection of cDNA (Table 1) were designed to amplify PCR products smaller than 200 bp because of the reported degradation and chemical modification of RNA recovered from FFPE samples (12).…”
mentioning
confidence: 99%
“…Although S. cerevisiae has several extracellular proteases (35), the proteolytic activity of C. albicans is significantly greater than that of S. cerevisiae because of the Sap family. In vitro, C. albicans can grow using proteins as a sole nitrogen source, whereas in vivo it survives in the blood stream utilizing serum albumin (36). In addition, the specific linker of our peptide was optimized for Sap isozymes.…”
Section: Design Of An Amp Activated By Virulent Proteases Discussionmentioning
confidence: 99%